A Longitudinal Evaluation of Goal-Striving Stress and Sleep Duration Among African Americans in the Jackson Heart Study. Issue 8 (October 2021) - Cain-Shields, Loretta R.; Johnson, Dayna A.; Glover, LáShauntá; Sims, Mario
ABSTRACT: Objective: The purposes of this study were to assess the association between changes in goal-striving stress (GSS) and changes in sleep duration in African Americans (AAs) and to determine if the association varies by sex, age, and/or educational attainment. Methods: We completed a longitudinal analysis using examination 1 (2000–2004, n = 5306) and examination 3 (2009–2013, n = 3819) data from the Jackson Heart Study, with a final sample of 3500. Changes in GSS and changes in sleep duration were calculated by subtracting examination 1 GSS from examination 3 GSS. Mean differences ( β [standard error]) between changes in GSS and changes in sleep duration were assessed using linear regression models that adjusted for length of follow-up, sociodemographics, health behaviors/risk factors, and stressors. Results: In the fully adjusted models, the increase in GSS from examination 1 to examination 3 was associated with a decrease in sleep duration (in minutes) from examination 1 to examination 3 in the overall cohort ( β = −7.72 [2.44], p < .002), in high school graduates ( β = −21.23 [5.63], p < .001), and in college graduates ( β = −7.57 [3.75], p = .044) but not in those with less than a high school education ( β = 1.49 [8.35], p = .86) or those who attended college but did not graduate ( β = 0.44 [4.94], p = .93). Conclusions: Changes in GSS were inversely associated with changes in sleep duration over a mean period of 8 years in AA subgroups. Interventions that reduce stress related to goal striving should be considered to help improve sleep health in AAs.